SCoT markers assisted evaluation of genetic diversity in new plant type (npt) lines of rice (Bangladesh Journal of Botany, 2022)
Rice being a stable food crop has wide range of diversity and distribution throughout the globe. Recently in hybrid rice breeding program new plant types have been developed through line x tester mating with the use of male sterility system. Genetic diversity and insight amplification among 43 New Plant Type (NTP) lines of rice using 15 start codon targeted polymorphism markers were tested. Out of 25 start codon targeted polymorphism (SCoT) primers, only 15 SCoT primers were amplified and produced 76 alleles with 83.26 per cent polymorphism. Average number of alleles per primer was 5.06, while polymorphism information content ranged from 0.28 to 0.67 with an average of 0.50 per primer. Dandogram cluster falls in two major group having 31 and 12 NPT lines respectively.Bangladesh J. Bot. 51(2): 335-341, 2022 (June)